Randomized, Double-Blinded, Placebo-Controlled Phase 2 Trial of an Inactivated Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine in Healthy Adults. (9th November 2020) - Che, Yanchun; Liu, Xiaoqiang; Pu, Yi; Zhou, Meijian; Zhao, Zhimei; Jiang, Ruiju; Yin, Zhifang; Xu, Mingjue; Yin, Qiongzhou; Wang, Jianfeng; Pu, Jing; Zhao, Heng; et al.
Abstract: Background: We evaluated an inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine for immunogenicity and safety in adults aged 18–59 years. Methods: In this randomized, double-blinded, controlled trial, healthy adults received a medium dose (MD) or a high dose (HD) of the vaccine at an interval of either 14 days or 28 days. Neutralizing antibody (NAb) and anti-S and anti-N antibodies were detected at different times, and adverse reactions were monitored for 28 days after full immunization. Results: A total of 742 adults were enrolled in the immunogenicity and safety analysis. Among subjects in the 0, 14 procedure, the seroconversion rates of NAb in MD and HD groups were 89% and 96% with geometric mean titers (GMTs) of 23 and 30, respectively, at day 14 and 92% and 96% with GMTs of 19 and 21, respectively, at day 28 after immunization. Anti-S antibodies had GMTs of 1883 and 2370 in the MD group and 2295 and 2432 in the HD group. Anti-N antibodies had GMTs of 387 and 434 in the MD group and 342 and 380 in the HD group. Among subjects in the 0, 28 procedure, seroconversion rates for NAb at both doses were both 95% with GMTs of 19 at day 28 after immunization. Anti-S antibodies had GMTs of 937 and 929 for the MD and HD groups, and anti-N antibodies had GMTs of 570 and 494 for the MD and HD groups, respectively. No serious adverse events were observed during the study period. Conclusions: Adults vaccinated with inactivated SARS-CoV-2 vaccine had NAb as well as anti-S/N antibody and had a low rate of adverse reactions. Clinical Trials Registration: NCT04412538. Abstract : An inactivated severe acute respiratory syndrome coronavirus 2 vaccine was evaluated in a randomized, double-blinded, placebo-controlled phase 2 trial involving 750 healthy adults. Serological detection of neutralizing antibodies and enzyme-linked immunosorbent assay antibodies and clinical observation indicated the immunogenicity and safety of the vaccine.